THEOKRASI DALAM KITAB HOSEA SEBAGAI PRINSIP KESETIAAN PENDETA DI DALAM PELAYANAN GEREJAWI - Padan, Stefanus (GENEVA: JURNAL TEOLOGI DAN MISI, 2025)
This research explores the concept of theocracy in the Book of Hosea as a principle of pastoral loyalty in ecclesiastical ministry. Using content analysis, it examines the relationship between God and His people under His direct rule. The study identifies three key aspects of theocracy in Hosea: warning, message, and restoration. The warning highlights the consequences of sin and deviation from theocracy, the message emphasizes God's unwavering love despite betrayal, and restoration reflects God's hope to restore broken relationships through repentance. The research also addresses the relevance of theocratic principles in modern ministry. Ideally, pastors should act as extensions of God, modeling faithfulness and integrity. However, challenges such as a lack of commitment and faithfulness under ministerial pressures are evident. Based on Hosea's theocratic principles, the study recommends that pastors strengthen their loyalty to God, focusing on integrity, obedience, and devotion to their congregation. The research confirms that ministry grounded in theocracy positively impacts the congregation's faith and glorifies God.